2014
DOI: 10.4097/kjae.2014.66.6.433
|View full text |Cite
|
Sign up to set email alerts
|

EC50and EC95of remifentanil to prevent rocuronium-induced withdrawal movements in children

Abstract: BackgroundIntravenous administration of rocuronium induces intense pain in most patients (60-100%). This could be harmful during anesthesia induction because of the unintended reflex movement of an unconscious patient in response to the pain. Previous studies have reported that remifentanil effectively reduces rocuronium-induced pain and withdrawal movements. This study was designed to evaluate the EC50 and EC95 of remifentanil to prevent withdrawal movements in children.MethodsWe enrolled a total of 171 pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Local mediators, such as kinins that directly irritate the venous nociceptors and the allogenic effect of aminosteroid neuromuscular blocking drugs were suggested as the possible mechanisms of rocuronium bromide-induced injection pain [16]. Park et al [17] demonstrated that remifentanil effectively prevents rocuronium-induced injection pain or withdrawal movement. Zhang et al [18] reported that the incidence and severity of rocuronium-induced injection pain were significantly alleviated by use of a large vein.…”
Section: Discussionmentioning
confidence: 99%
“…Local mediators, such as kinins that directly irritate the venous nociceptors and the allogenic effect of aminosteroid neuromuscular blocking drugs were suggested as the possible mechanisms of rocuronium bromide-induced injection pain [16]. Park et al [17] demonstrated that remifentanil effectively prevents rocuronium-induced injection pain or withdrawal movement. Zhang et al [18] reported that the incidence and severity of rocuronium-induced injection pain were significantly alleviated by use of a large vein.…”
Section: Discussionmentioning
confidence: 99%
“…In the first article, Park et al [ 1 ] stated that some previously reported confidence intervals for 95% thresholds estimated with the up-and-down sequential (UDS) design were so large that they demonstrated a fixed-concentration design. While the text comprises a matter-of-fact description, those are also intriguing me to regard as their confession, in a sense.…”
mentioning
confidence: 99%